Crowdsourcing em museus: contribuições para a preservação do patrimônio na WEB 2.0 - Tatiana Mara Alves Martins (2017)
The present research, in the light of Information Science, studies the potential of integration of the informational crowdsourcing phenomenon in museums, focusing on the contributions of its use to the strengthening of the institutions acting as a path of innovation of its practice in the information society, through web 2.0. SWOT (Strengths and Weaknesses, Opportunities and Threats) - analysis of the reference documents of museology: Santiago Round Table, ICOM-1972, Quebec Declaration, Basis Principles of a New Museology-1984 and the Declaration of Caracas- ICOM 1992. It is a case study, with the hypothesis: crowdsourcing (CS) contributes to the realization of the social function of museums in web 2.0. And as a result, the understanding that crowdsourcing contributes to the exploitation as potentialities (strengths and opportunities) and to the risks (external risks and threats) experienced for museums, besides the proposal of a script or model of use of CS for Brazilian museums, Since this strategy is little studied, divulged and practiced by museums, mainly in Brazil.